The Synthesis and Spectral Properties of Benzofuran Derivative bis-Chalcone - Neslihan Beyazit (Hittite Journal of Science and Engineering, 2018)
Khellin, a natural furanochromone, was isolated from the fruits of Ammi visnaga L. by using a rapid and easy technique. It was then hydrolyzed with 10% KOH to obtain khellinone. From the Claisen-Schmidt condensation of khellinone with terephthalaldehyde, a new benzofuran derivative bis-chalcone was synthesized and its spectroscopic properties were investigated in details.